Peru's road to climate action: Are we on the right path? The role of life cycle methods to improve Peruvian national contributions - Vázquez-Rowe, I.; Kahhat, R.; Larrea-Gallegos, G.; Ziegler-Rodriguez, K. (Elsevier, 2019)
Most developing nations have had to perform a swift transition from the voluntary greenhouse gas (GHG) emissions mitigation actions engaged in the Copenhagen Accord, to the relatively ambitious mitigations signed in the frame of the Paris Agreement. Consequently, Peru is currently creating its national structure to combat climate change through mitigation and adaptation actions. Nationally-determined contributions (NDCs) are the planned interventions that nations report for intended reductions in GHG emissions. In fact, Peru has now committed to reduce its annual GHG emissions by 30% in 2030 with respect to a business-as-usual estimation for that same year. The 76 NDCs have been divided into six main sectors: energy, transport, industrial processes, agriculture, forestry and waste. In this context, the main goal of this study is to provide a critical review of the validity and effectiveness of current mitigation NDCs proposed by the Peruvian government to comply with the Paris Agreement. Moreover, the analysis is accompanied by a discussion on how the use of life-cycle methods, namely Life Cycle Assessment, can be of utility in terms of policy support to evaluate the mitigation potential of these NDCs, as well as in the identification of additional contributions in sectors where the mitigation potential has been obviated. The expansion of system boundaries beyond the national context to account for the globalized nature of current market flows or the modelling of indirect impacts of a particular policy appear as relevant advantages of including life-cycle methods in public climate policy. The analysis, which is intended to be of utility to policy-makers in Peru and in other developing and emerging economies across the world, suggests that life-cycle methods arise as adequate tools to monitor the environmental appropriateness of adopting or adapting low-carbon technology to the local context.
Keywords: Greenhouse gas; Context (archaeology); Life-cycle assessment; Climate change mitigation; Climate change; Government (linguistics); Environmental planning; Natural resource economics; Business; Environmental resource management; Economics; Environmental science; Geography; Production (economics); https://purl.org/pe-repo/ocde/ford#5.02.05